THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP SCHOOL PRINCIPALS AND TEACHERS' EMOTIONAL INTELLIGENCE ON THE PROFESSIONAL COMPETENCE OF PRIMARY SCHOOL TEACHERS - NOFITA, Eka (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2023)
This research aims to examine the influence of principals' transformational leadership and teachers' emotional intelligence on the professional competence of state elementary school teachers in Beji Depok District. The method used is a quantitative method using a causal survey method with a path analysis approach. The population in this study was 168 public elementary school teachers in Beji Depok District. The sample amounted to 1141 using the formula developed by Slovin. Data analysis techniques using SPSS. The conclusions of this research are: 1) There is a positive and significant influence of the principal's transformational leadership on the professional competence of public elementary school teachers, 2) There is a positive and significant influence of teacher emotional intelligence on the professional competence of public elementary school teachers. and 3) There is a positive and significant influence of the Principal's transformational leadership on the emotional intelligence of state elementary school teachers. The implications of this research are: 1) The implications of increasing teacher professional competence by optimizing the transformational leadership of school principals through: influencing charismatically, inspiring, stimulating and providing individual sensitivity. 2) The implications of increasing teacher emotional intelligence through: providing self-awareness, managing one's emotions, motivating oneself, recognizing other people's emotions and demonstrating social skills. 3) The implications of increasing teachers' emotional intelligence by optimizing the head's transformational leadership, for example by providing: role models for teachers, providing clear direction and instructions for teachers and rewarding teachers who can manage their emotional intelligence better.